Geospatial Variability Mapping of Soil Properties in Kukra Block of Muzaffarnagar District and its Impact on Agricultural Productivity - Singh, Avitansh; Bharteey, P. K.; Singh, G.; Bahuguna, A.; Luthra, N.; Pal, S. (International Journal of Bio-resource and Stress Management, 2025)
The study was carried out in various villages of the Kukra block in Muzaffarnagar district-251001, Uttar Pradesh, India, from November, 2023 to June, 2024 to assess the soil properties and to prepare soil fertility maps of the area. Thirty-five (35) soil samples were collected from a depth of 0–15 cm utilising a random sampling method. Subsequently, soil samples were air-dried in the shade at ambient temperature and subjected to screening through a 2 mm mesh for nutrient analysis. Fifteen soil properties, namely sand, silt, clay, bulk density (BD), particle density (PD), porosity, pH, electrical conductivity (EC), organic carbon (OC), nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulphur (S) were assessed. The findings revealed that the soils examined varied from neutral to slightly salinised. 80% and 20% of the soil samples, respectively, were predominantly neutral and free from salinity hazards. Samples exhibited low, medium, and high concentrations of organic carbon. Soil organic carbon concentration is characterised as 48.57% low, 28.57% medium, and 22.86% high. Samples exhibited low and medium concentrations of accessible nitrogen (34.29% and 65.71%, respectively) in the soil. The phosphorus level in the soil samples was categorised as low (11.43%), medium (45.71%), and high (42.86%). The results for available sulphur were medium at 88.57% and high at 11.43%, respectively. The soil samples contained sufficient exchangeable calcium and magnesium.